2009
DOI: 10.2527/jas.2009-2060
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid digestibility and energy concentration in a novel source of high-protein distillers dried grains and their effects on growth performance of pigs

Abstract: Three experiments were conducted to evaluate a novel source of high-protein distillers dried grains produced by Buhler Inc. (HP-DDG(Buhler)) and fed to growing pigs. The standardized ileal digestibility (SID) of AA in HP-DDG(Buhler) and in soybean meal (SBM) was determined in Exp. 1. Nine pigs (109.8 +/- 2.78 kg of BW) were fitted with a T-cannula in the distal ileum and allotted to a triplicated 3 x 3 Latin square design with 3 diets and 3 periods per square. Diets containing HP-DDG(Buhler) or SBM as the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
62
5
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 14 publications
19
62
5
2
Order By: Relevance
“…Groups A and B were supplemented with l-lysine, l-methionine, l-threonine, and l-tryptophan (see Table 1 Group A = 10 % CP (very low CP level); Group B = 13 % CP (low CP level); Group C = 16 % CP (normal CP level). Groups A and B were supplemented with l-lysine, l-methionine, l-threonine, and l-tryptophan (see Table 1 Kim et al 2009). However, maximal growth performance and feed efficiency of pigs depend on adequate provision of AA that can be synthesized by animals (Hou et al 2013(Hou et al , 2015Wu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Groups A and B were supplemented with l-lysine, l-methionine, l-threonine, and l-tryptophan (see Table 1 Group A = 10 % CP (very low CP level); Group B = 13 % CP (low CP level); Group C = 16 % CP (normal CP level). Groups A and B were supplemented with l-lysine, l-methionine, l-threonine, and l-tryptophan (see Table 1 Kim et al 2009). However, maximal growth performance and feed efficiency of pigs depend on adequate provision of AA that can be synthesized by animals (Hou et al 2013(Hou et al , 2015Wu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Liener (1972) and Kim et al (2009) also reported that overheating made lysine unavailable due to its interaction with the reducing groups of sugars, called Maillard reactions, and thus it was no longer susceptible to tryptic cleavages making it unavailable to the pig. In the current study, the AID and SID of isoleucine, leucine, lysine, threonine, and valine in diets and corn were reduced by dehulled-extrusion processing, but not in extruded corn or extruded corn diet.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids (AA) have enormous physiological importance and considered as structural units for tissue proteins and essential substrates for many low molecular weight substances (Kim et al, 2009;Wu et al, 2014). Increasing interest in AA nutrition research reflects their importance to enhance animal production in a global context .…”
Section: Growth and Development Of Skeletal Musclementioning
confidence: 99%